A "Financialised Production of Space". Analysing Real Estate Investment Funds through Lefebvre's Spatial Triad. Issue 3 (27th May 2022) - Toro, Fernando; Navarrete-Hernandez, Pablo
ABSTRACT: This research contributes to gaining a deeper understanding of the nature of the financialization of the built environment from a spatial dimension. Empirical studies have predominantly used a quantitative approach to explore these processes. In contrast, this article seeks a better understanding of the ways in which financial institutions conceive of and represent space. Through the lens of Lefebvre's spatial triad, we analyse in-depth interviews with key high-level investment fund managers, along with the annual reports of three investment funds operating in Santiago, Chile. Our thematic analysis reveals a potential "financialised production of space" and indicates that data can be classified into three distinct categories: commodification of the material space, codification of the representation of space and, the subjectification of the representational space. The study concludes that investment funds construct financial spatial narratives, through which space is disembodied and conceived as a commodity,  represented in the form of pictures and codes.